2015
DOI: 10.1108/mhrj-08-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable staff well-being within older adult mental health

Abstract: Purpose -The purpose of this paper is to explore how staff attend to their well-being when working in an inpatient mental health setting with older adults with dementia and complex mental health needs; how staff understand the link between their well-being and the well-being of patients. Design/methodology/approach -A semi-structured group interview was held with 11 members of two multidisciplinary teams. The discussion was audio-recorded and analysed using thematic analysis. Findings -Staff reported managing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Gold standard ‘person-centred care’ is underpinned by empathy towards the person with dementia and is reliant upon direct and meaningful engagement, with value being attributed, and the ability to view the world from their perspective [2, 15, 16]. However, the healthcare experiences of many people with dementia in the community and in hospital are often poor [17] with an over-reliance on task-oriented, as opposed to compassionate care [18].…”
Section: Introductionmentioning
confidence: 99%
“…Gold standard ‘person-centred care’ is underpinned by empathy towards the person with dementia and is reliant upon direct and meaningful engagement, with value being attributed, and the ability to view the world from their perspective [2, 15, 16]. However, the healthcare experiences of many people with dementia in the community and in hospital are often poor [17] with an over-reliance on task-oriented, as opposed to compassionate care [18].…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic medication used to treat distress behaviours have significant adverse effects, including increased mortality. 9 , 10 Calls for increased implementation of nonpharmacological interventions have been made. Our findings suggest that music therapy may be an effective nonpharmacological treatment for BPSD, with a significant reduction of distress behaviours on days of in-person intervention delivery shown, supported in the qualitative data, with lasting changes to patient mood and levels of agitation reported by music therapists and staff members.…”
Section: Discussionmentioning
confidence: 99%
“…5 The impact on staff is important as research has long shown a close link between staff well-being, including job satisfaction and coping mechanisms, and patient well-being. 10,11 However, very little research has investigated nonpharmacological interventions for this setting, despite calls for more research in this area. 12 During the COVID-19 pandemic, service provision changed drastically.…”
mentioning
confidence: 99%
“…‘opportunity for staff “to be heard, and to have your ideas put forward” (P2) regarding patients’ care’. Blagg and Petty (2015)…”
Section: Methodsmentioning
confidence: 99%